Traditions of Folk Medicine in Georgia and Perspectives of Using Natural Medicinal Plants - Elizbarashvili, Nodar; Gurgenidze, Miranda; Elizbarashvili, Rusudan; Bubashvili, Luiza (Global Journal Of Botanical Science, 2023)
The treatment methods and knowledge accumulated in Georgia over the centuries are related to the country’s geographical location, diverse nature, traditions, history and knowledge of the use of medicinal products. The article discusses a brief history of the development of folk medicine in Georgia, the medicinal plants that have been used in traditional medicine for centuries, the biological and landscape diversity of the country, the geographical features of the distribution of some medicinal plants and their main medicinal purpose, the economic importance of medicinal plants and the problems associated with their extraction.